2021
DOI: 10.1186/s12889-021-10950-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of non-pharmaceutical public health interventions on COVID-19 epidemics in the United States

Abstract: Background The widespread pandemic of novel coronavirus disease 2019 (COVID-19) poses an unprecedented global health crisis. In the United States (US), different state governments have adopted various combinations of non-pharmaceutical public health interventions (NPIs), such as non-essential business closures and gathering bans, to mitigate the epidemic from February to April, 2020. Quantitative assessment on the effectiveness of NPIs is greatly needed to assist in guiding individualized decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…Specifically, a natural experiment across 200 countries showed 45.7% fewer covid-19 related mortality in countries where mask wearing was mandatory (table 1). 49 Another natural experiment study in the US reported a 29% reduction in SARS-CoV-2 transmission (measured as the time varying reproductive number Rt) (risk ratio 0.71, 95% confidence interval 0.58 to 0.75) in states where mask wearing was mandatory 58…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, a natural experiment across 200 countries showed 45.7% fewer covid-19 related mortality in countries where mask wearing was mandatory (table 1). 49 Another natural experiment study in the US reported a 29% reduction in SARS-CoV-2 transmission (measured as the time varying reproductive number Rt) (risk ratio 0.71, 95% confidence interval 0.58 to 0.75) in states where mask wearing was mandatory 58…”
Section: Resultsmentioning
confidence: 99%
“…All the studies that assessed stay at home or isolation measures reported reductions in transmission of SARS-CoV-2 (table 2). A retrospective cohort study from the US reported a significant reduction in the odds of having a positive reproductive number (R0) result (odds ratio 0.07, 95% confidence interval 0.01 to 0.37),41 and a natural experiment reported a 51% reduction in time varying reproductive number (Rt) (risk ratio 0.49, 95% confidence interval 0.43 to 0.54) 58…”
Section: Resultsmentioning
confidence: 99%
“…All studies reported a protective benefit in terms of either reduced incidence, mortality, hospitalization, or a combination of these outcomes. This review summarized the literature up to March 2021, since which time a number of additional studies have reported a protective benefit impact of community mask wearing by the general public in community settings using ecological data [42] , [43] , [44] , [45] , [46] . While the results of these individual studies support the findings of this review, the large amount of research being done to assess community mask wearing warrants future systematic assessment.…”
Section: Discussionmentioning
confidence: 99%
“… Houston, Texas, May 1, 2020 – June 29, 2020 risk-stratified SIR-HCD The proposed model obtained lower mean squared error (MSE) and higher prediction accuracy compared to other models, and supports counterfactual analysis. Liu et al (May 2021) [150] investigate the influence (reproduction number) of non-pharmaceutical public health interventions on COVID-19 epidemics in the United States COVID Tracking Project ( https://covidtracking.com ) a generalized linear model (GLM) Different NPIs showed different levels of reproduction numbers. The stay-at-home played the most important role and contributed approximately 51% (95% CI 46%-57%).…”
Section: Ai In Covid-19 Therapeutics: Drug Discoverymentioning
confidence: 99%